Comparative Analysis of Mitogenomic and Nuclear Gene Data Reveals Phylogenetic Implications, Divergence Times, and Historical Biogeography in the Subfamily Pyrginae (Lepidoptera: Hesperiidae) - Jintian Xiao; Xiangyu Hao; Hideyuki Chiba; Yiping Li; Xiangqun Yuan (Ecology and Evolution)
ABSTRACT The subfamily Pyrginae sensu lato (Lepidoptera: Hesperiidae) represents a group of skipper butterflies, consisting of 1132 species in 153 genera and nine tribes. Although the phylogeny and morphology of Pyrginae have been extensively studied, there is limited information on their historical biogeography. Evolutionary relationships among hesperiid subfamilies and tribes are prerequisites for inferring their biogeographic patterns. In this study, the complete mitochondrial genomes of 10 Hesperiidae, in which seven Pyrginae, were newly sequenced. Our sampling encompassed 118 species, including 93 Pyrginae, representing nine tribes and 85 genera. A concatenated super‐matrix of mitogenomic data and the nuclear genes EF‐1α and Wingless was constructed. The monophyly of Pyrginae was robustly supported (PP = 1, BP = 89). Within Pyrginae, relationships among Tagiadini, Pyrrhopygini, Jerini, and Celaenorrhinini were stable, while relationships among Pyrgini, Carcharodini, Erynnini, and Achlyodidini varied, requiring further study. The most recent common ancestor of Pyrginae sensu lato was inferred to have been distributed in the Neotropical region or the Neotropical region + the Palearctic region in the early Paleocene (ca. 56.31 Ma) while that of Pyrginae sensu stricto (Achlyodidini, Pyrgini, Carcharodini, and Erynnini) was in the Neotropical region in the early Eocene (ca. 46.72 Ma).